If you cannot agree, move on! On labels and non-nominative subjects. Issue 1 (23rd February 2018) - Citko, Barbara; Germain, Allison; Witkoś, Jacek
Abstract : This paper examines the predictions of Chomsky's (2013 ; 2015 ) Labeling Algorithm for structures with non-nominative, non-agreeing elements in what looks like a subject position: since such non-nominative subjects do not agree with the verb, the resulting structure cannot be labeled through feature sharing. Thus, the only option for such subjects is to move from [Spec, TP] or never land there. We argue for the latter option, motivating it for PPs in Polish locative inversion, instrumental DPs in Polish predicate inversion, dative subjects in Russian and Polish, genitive subjects in Lithuanian Inferential Evidentials, and accusative DPs in Russian and Polish Adversity Impersonals. We conclude by showing that under certain very restricted circumstances (i.e. when partial Agree takes place or Agree for structural case holds but Agree for phi-features is attempted and fails for independent reasons), the non-nominative elements can remain in [Spec, TP].